Organizational correlates of service availability in outpatient substance abuse treatment programs. - Edwards JR; Knight DK; Flynn PM; Edwards, Jennifer R; Knight, Danica K; Flynn, Patrick M (Journal of Behavioral Health Services & Research, 2011)
In pursuit of quality care for drug abuse treatment programs, researchers continue to monitor program characteristics related to service provision. The current study examines 115 outpatient drug-free programs in four U.S. regions and documents typical methods of offering an array of services and the relationship between program characteristics and services offered onsite and by referral. Core services (e.g., comprehensive assessments) are offered primarily onsite, whereas delivery methods of wraparound services are mixed with transitional services offered generally onsite and medical services traditionally offered offsite. Accredited programs offered more core services onsite, while those providing case management offered more core and wraparound services onsite. Programs with a higher proportion of dually diagnosed clients offered more core services onsite and fewer wraparound services by referral. Programs with a higher concentration of criminal justice-referred clients offered fewer core services onsite. These findings suggest ways of improving access to services.